The Influence of Principal’s Leadership and Work Motivation on High School Teacher’s Performance - Beliani, Karespa (PPSDP International Journal of Education, 2024)
This quantitative study aims to examine the principal’s leadership and work motivation on high school teacher’s performance. The result stated that the administration that supports the learning implementation process is complete and well organized, as evidenced by the results of supervision from the principal to all teachers whose results are very good, the competence and performance of teachers have increased. This is because the implementation of academic supervision is really prepared and programmed, so that the principal and teacher realize that the academic supervision program helps in learning. The results of the supervision implementation are followed up to improve the implementation of further academic supervision.